UTILIZATION OF LIPID AS DIETARY ENERGY SOURCE FOR FINGERLINGS OF CHANNA STRIATUS - A. Jesu Arockia, Raj; M.A, Haniffa; S, Seetharaman; P, Perumalsamy (Malaysian Journal of Science, 2004)
An experiment was carried out to determine the dietary lipid requirement of the fingerlings of the striped murrel Channa striatus. Cod liver oil was used as a source oflipid and six crude lipid levels (7.54 - 22.3%) and energy levels (3.54 - 4.38 kcal/g) were selected. Each diet was given as 3% of total wet body weight in two equal rations to triplicate groups of 20 fingerlings with an average individual weight of 0.62 Ã‚Â± 0.22g in cement aquaria (capacity: 500 l) for 8 weeks. Growth rate was the highest in fingerlings fed at 13.54% lipid diet, where the conversion was the lowest (1.33) and the specific growth rate was the highest (2.15o/oIday). Dietary lipid produced a significant difference in the growth of C. striatus.